Intratumoral budding is associated with poor clinical outcome in early‐stage clear cell carcinoma of ovary. Issue 6 (22nd September 2021) - Lin, Lawrence Hsu; Zamuco, Ronaldo DeLeon; Shukla, Pratibha Sharma
Abstract : Aims: Clear cell carcinoma of ovary (CCC) is considered a high‐grade malignancy by default and the role of histological grading for assessing clinical outcome is not established. We aimed to evaluate histopathological features associated with clinical outcome in CCC patients. Methods and results: Seventy‐six cases of CCC with available clinical follow‐up information were studied. Histopathological features, including tumour size, architectural patterns, nuclear atypia, mitotic activity, intratumoral and peritumoral inflammation, presence of endometriosis, peritumoral and intratumoral budding, were evaluated. Multivariate analysis was performed with logistic regression and Kaplan–Meier survival curves with the log‐rank test were used for survival analysis. Forty cases (53%) presented at stage I. Complete response to treatment was achieved in 65%, while 35% of patients had tumour recurrence or progression of disease despite treatment. At last follow‐up, 13% had died of disease, 20% were alive with disease and 67% had no evidence of disease. Higher stage ( P = 0.0016) and presence of intratumoral budding ( P = 0.0454) were independently associated with recurrence/disease progression. Advanced stage ( P = 0.0011), presence of lymph node involvement ( P = 0.0003), intratumoral budding ( P = 0.0023) and peritumoral budding ( P = 0.0334) were significantly associated with shorter survival. Intratumoral budding was significantly associated with recurrent/progressive disease ( P = 0.0195) and also shorter survival ( P = 0.0277) within the cohort of low‐stage (I/II) patients as well. Conclusion: We have shown that besides the classic prognostic factors of stage and lymph node status, the presence of tumour budding is associated with poorer outcome in patients with CCC. Specifically, evaluation of intratumoral budding may help to more clearly predict prognosis in patients with early‐stage disease. Abstract :